2002
DOI: 10.1124/jpet.301.2.578
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Influences of Heavy Metals on Anionic Drug Efflux from Renal Proximal Tubule

Abstract: We recently demonstrated in isolated killifish renal proximal tubules that two classes of nephrotoxicants, aminoglycoside antibiotics and radiocontrast agents, rapidly decrease transport mediated by multidrug resistance protein 2 (Mrp2) by causing endothelin (ET) release and signaling through an ET B receptor and protein kinase C (PKC) Terlouw et al., 2001). In the present study, we used killifish proximal tubules, fluorescein methotrexate, a fluorescent model substrate for Mrp2, and confocal microscopy to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
41
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 34 publications
10
41
0
Order By: Relevance
“…Previous studies on FL-MTX transport in killifish renal tubules have shown high inhibitory potencies of Mrp2 substrates and inhibitors in this process (25,26), as well as enhanced FL-MTX transport in vesicles overexpressing Mrp2 (49), thus confirming that FL-MTX transport in this assay is indeed mediated through Mrp2. The PTHrP used in this study was sea bream (Sparus auratus) recombinant PTHrP (resbPTHrP) (13,14).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies on FL-MTX transport in killifish renal tubules have shown high inhibitory potencies of Mrp2 substrates and inhibitors in this process (25,26), as well as enhanced FL-MTX transport in vesicles overexpressing Mrp2 (49), thus confirming that FL-MTX transport in this assay is indeed mediated through Mrp2. The PTHrP used in this study was sea bream (Sparus auratus) recombinant PTHrP (resbPTHrP) (13,14).…”
supporting
confidence: 66%
“…Analogous to the results presented here, we predict that other calciotropic hormones, such as calcitonin and calcitriol, may influence organic anion transport. As mentioned before, these hormones influence [Ca 2ϩ ] i and/or use [Ca 2ϩ ] i as a second messenger (23,39,57,58), and high medium calcium levels are known to reduce Mrp2-mediated transport (48,49). Euryhaline fish such as sea bream and killifish easily adapt to waters with different salinities and calcium contents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversially, cadmium salt (CdCl 2 ) was found not to be an inducer for Abcc2 expression in primary rat hepatocytes (Vernhet et al, 2001), but it was demonstrated to induce Abcc2 expression in isolated killifish renal proximal tubules (Terlouw et al, 2002). In this study, exposure to mercury and lead significantly induced the expression of zebrafish abcc2 gene; however, as analyzed with WISH, cadmium and arsenate displayed no induction effects on the expression of abcc2 in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 52%